FBXO28 causes developmental and epileptic encephalopathy with profound intellectual disability. (6th December 2020) - Schneider, Amy L.; Myers, Candace T.; Muir, Alison M.; Calvert, Sophie; Basinger, Alice; Perry, M. Scott; Rodan, Lance; Helbig, Katherine L.; Chambers, Chelsea; Gorman, Kathleen M.; King, Mary D.; Donkervoort, Sandra; et al.
Abstract: Chromosome 1q41‐q42 deletion syndrome is a rare cause of intellectual disability, seizures, dysmorphology, and multiple anomalies. Two genes in the 1q41‐q42 microdeletion, WDR26 and FBXO28, have been implicated in monogenic disease. Patients with WDR26 encephalopathy overlap clinically with those with 1q41‐q42 deletion syndrome, whereas only one patient with FBXO28 encephalopathy has been described. Seizures are a prominent feature of 1q41‐q42 deletion syndrome; therefore, we hypothesized that pathogenic FBXO28 variants cause developmental and epileptic encephalopathies (DEEs). We describe nine new patients with FBXO28 pathogenic variants (four missense, including one recurrent, three nonsense, and one frameshift) and analyze all 10 known cases to delineate the phenotypic spectrum. All patients had epilepsy and 9 of 10 had DEE, including infantile spasms (3) and a progressive myoclonic epilepsy (1). Median age at seizure onset was 22.5 months (range 8 months to 5 years). Nine of 10 patients had intellectual disability, which was profound in six of nine and severe in three of nine. Movement disorders occurred in eight of 10 patients, six of 10 had hypotonia, four of 10 had acquired microcephaly, and five of 10 had dysmorphic features, albeit different to those typically seen in 1q41‐q42 deletion syndrome and WDR26 encephalopathy. We distinguish FBXO28 encephalopathy from both of these disorders with more severe intellectual impairment, drug‐resistant epilepsy, and hyperkinetic movement disorders.